The EU Declaration on the legal consequences of the Komstroy judgment on intra-EU arbitration under the Energy Charter Treaty - Rueda García, José Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The EU, EURATOM and their Member States issued a Declaration in June 2024 following the CJEU’s Komstroy judgment with a view to neutralizing the use of the Energy Charter Treaty by investors of Member States of the EU to claim in arbitration proceedings against another Member State. The Declaration tackles not only the commencement of new cases but also pending claims in which the tribunal may still have to decide on its jurisdiction or in which a court may be seized to enforce an intra-EU award. The failure of previous declarations and the subsequent adoption of an amendment to the ECT and an inter-se treaty on this matter cast serious doubts about the practical impact and success of the Declaration as such.
Keywords: Energy Charter Treaty; Intra-EU arbitration; EU law; Komstroy; Bilateral investment treaties; Achmea